Polyamide-polycarbonate composite material, preparation method thereof and component

By polymerizing caprolactam, polycarbonate and activator in the presence of a catalyst, a polyamide-polycarbonate composite material with higher molecular weight was prepared, which solved the thermal stability and water absorption of cast nylon in special environments, and achieved the efficient impact resistance and low water absorption characteristics of the material.

CN119842215APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311346252.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Cast nylon has problems such as poor thermal stability, poor dimensional stability, poor low temperature toughness and high water absorption in certain special environments, which affects its application in industrial production.

Method used

Polyamide-polycarbonate composite materials with higher molecular weight were prepared by polymerizing molten caprolactam, polycarbonate and activator in the presence of a catalyst. The method includes the transesterification reaction between the polycarbonate prepared by the transesterification method and the generated polyamide to form block copolymers and improve the compatibility and physical properties of the material.

Benefits of technology

The impact strength of the polyamide-polycarbonate composite material is improved and its saturation water absorption is reduced, thereby improving the thermal stability, dimensional stability and low-temperature toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842215A_ABST
    Figure CN119842215A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer composite materials, and discloses a polyamide-polycarbonate composite material, a preparation method thereof and a component. The preparation method of the polyamide-polycarbonate composite material comprises the following step: in the presence of a catalyst, carrying out polymerization reaction on molten caprolactam, polycarbonate and an activating agent to obtain the polyamide-polycarbonate composite material. The IZOD notch impact strength of the polyamide-polycarbonate composite material prepared by the invention is 6.7 to 7.7 kJ / m < 2 >, the saturated water absorption rate is 3.5 to 4.6 percent, and the viscosity average molecular weight is 78600 to 83100g / mol. When the polyamide-polycarbonate composite material disclosed by the invention is applied to manufacturing components with complex structures, such as gears, propellers, sealing rings and impellers, the polyamide-polycarbonate composite material has relatively high impact strength, relatively low saturated water absorption rate and relatively stable dimensional stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer composite materials, in particular to a polyamide-polycarbonate composite material and a preparation method and a component thereof. Background Art

[0002] Among all engineering plastics, polyamide is the first one to be developed, and its output and consumption rank first among all engineering plastics. The most common polymerization methods of nylon include polycondensation of diamine and dibasic acid, ring-opening polymerization of cyclic amide and polycondensation of amino acid. Compared with other types of engineering plastics, polyamide has better mechanical properties, thermal stability, corrosion resistance, oil resistance, wear resistance and self-lubrication. These properties have promoted the application and development of nylon, which is widely used in machinery industry, electronic appliances, national defense security, transportation and industrial production.

[0003] Cast nylon has attracted the attention of researchers due to its excellent performance. Due to the difference in polymerization methods, compared with common nylon, cast nylon has a larger molecular weight, higher crystallinity, and has the advantages of vibration absorption, high mechanical strength, self-lubrication and good wear resistance. Therefore, it is widely used in aerospace and industrial production. At the same time, due to the particularity of its molding, cast nylon is often used to manufacture components with relatively complex structures, such as gears, propellers, sealing rings and impellers. However, in some special environments, unmodified cast nylon has some obvious defects, such as poor thermal stability, poor dimensional stability, poor low-temperature toughness and high water absorption, which seriously affect the application of cast nylon in industrial production. Therefore, solving the problems of poor impact and high water absorption of cast nylon is the only way to expand the use of nylon. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor impact strength, high saturated water absorption and poor dimensional stability of cast nylon in the prior art, and to provide a polyamide-polycarbonate composite material and a preparation method and component thereof.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a polyamide-polycarbonate composite material, wherein the method comprises:

[0006] In the presence of a catalyst, molten caprolactam, polycarbonate and an activator are polymerized to obtain the polyamide-polycarbonate composite material.

[0007] The second aspect of the present invention provides a polyamide-polycarbonate composite material prepared by the preparation method.

[0008] A third aspect of the present invention provides a component, wherein the component is formed by molding the polyamide-polycarbonate composite material.

[0009] Preferably, the component is selected from one or more of a gear, a propeller, a sealing ring, and an impeller.

[0010] Through the above technical scheme, in a water-free and impurity-free environment, under the action of an alkaline catalyst, the amide monomer is converted into an amide monomer salt, and under alkaline conditions, the amide monomer salt dissociates into an amide monomer anion, and then an anionic polymerization growth reaction is carried out, wherein the small molecular monomer H2O generated in the reaction will be removed as the vacuum is drawn, thereby ensuring the smooth progress of the reaction. Secondly, the amide monomer interacts with the activator added later to obtain a monomer containing an imide structure with strong electrophilic properties, which can become a chain initiation center. For anionic polymerization, the activity of the anion has a decisive influence on the reaction rate. The active center accelerates the reaction and promotes the growth of the molecular chain. The roles and effects of the alkaline catalyst and the activator in the polymerization process of caprolactam are shown in Table 1. It can be seen from Table 1 that when the alkaline catalyst is not added to the reaction system (Comparative Example 2), the polymerization reaction cannot proceed; when the activator is not added to the reaction system (Comparative Example 3), the polymerization reaction proceeds relatively slowly. Under the same other reaction conditions, the viscosity average molecular weight of the composite material (polyamide) obtained in Comparative Example 3 is 11200 g / mol, which is much smaller than the viscosity average molecular weight of the composite material (polyamide) obtained in Examples 1-5. It can be seen that the polyamide prepared by the method of the present invention has a higher molecular weight than the conventional polyamide prepared by polycondensation, thereby improving the physical properties of the polyamide in terms of rigidity, toughness, friction resistance, water absorption, etc. Again, the present invention adds a dissolving solution containing polycarbonate to the molten caprolactam, so that the polycarbonate is evenly dispersed in the molten caprolactam, and the water carried in the raw material, the chloroform in the solution, and the water generated in the generation process of the caprolactam anion are removed by vacuuming. During the polymerization reaction, the polycarbonate is dissolved in the caprolactam, and as the caprolactam generates polyamide through polymerization, the polycarbonate is evenly dispersed in the polyamide, thereby improving the compatibility between the polyamide and the polycarbonate, so that the polycarbonate improves the impact strength of the polyamide and reduces its saturated water absorption rate; in addition, in the composite material, the improvement of the compatibility between the polyamide and the polycarbonate also reduces the gap in the composite material obtained by the present invention, further promoting the reduction of the water absorption rate of the composite material. In addition, during the polymerization process of caprolactam, an ester exchange side reaction occurs between the polycarbonate obtained by the ester exchange method and the generated polyamide, and the generated polyamide-polycarbonate block copolymer can promote the compatibility between the polyamide and the polycarbonate in the composite material, further improving the impact strength of the composite material, and further reducing its saturated water absorption rate. It can be seen from Table 1 that the uniform doping of the polycarbonate prepared in Examples 1-5 can improve the compatibility between polycarbonate and polyamide, increase the impact strength of the composite material, and reduce its saturated water absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is the infrared spectrum of substance m1 obtained in Example 1;

[0012] Figure 2 is the infrared spectrum of substance m2 obtained in Example 1;

[0013] Figure 3 This is the infrared spectrum of substance m3 obtained in Example 1. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0016] A first aspect of the present invention provides a method for preparing a polyamide-polycarbonate composite material, wherein the method comprises:

[0017] In the presence of a catalyst, molten caprolactam, polycarbonate and an activator are polymerized to obtain the polyamide-polycarbonate composite material.

[0018] According to the preparation method of the present invention, in order to make polycarbonate more easily undergo ester exchange reaction with polyamide and improve the compatibility between the two, preferably, the polycarbonate is an aromatic polycarbonate prepared by ester exchange method.

[0019] Further preferably, the aromatic polycarbonate has a plurality of benzene rings in its molecular structure, and has a melt index of 5-15 g / 10 min at 300° C. and a load of 1.2 kg.

[0020] In some embodiments of the present invention, the polycarbonate is an ester-exchanged bisphenol A polycarbonate resin, and the model is PC02-10.

[0021] According to the preparation method of the present invention, in order to ensure that the prepared polyamide-polycarbonate composite material maintains the original excellent properties of polyamide, and at the same time, utilizes polycarbonate to improve the impact strength of the composite material and reduce its water absorption, preferably, the weight ratio of the caprolactam monomer to the polycarbonate is 100:2-8.

[0022] In some embodiments of the present invention, the weight ratio of caprolactam to the polycarbonate is 100:5, 100:2 or 100:8, respectively.

[0023] According to the preparation method of the present invention, in order to make the amide monomer react to form an amide salt, and dissociate into an amide anion in an alkaline environment to ensure the smooth progress of the anionic polymerization reaction, preferably, the catalyst is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide, and sodium methoxide, wherein the weight ratio of the catalyst to caprolactam is 0.15-0.25:100.

[0024] In some embodiments of the present invention, the catalyst is sodium hydroxide, and the weight ratio of the catalyst to caprolactam is 0.15:100, 0.2:100 or 0.25:100.

[0025] According to the preparation method of the present invention, in order to better activate the caprolactam monomer to become the center of chain initiation and promote the growth of molecular weight, preferably, the activator is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl isocyanate, and hexamethylene diisocyanate, wherein the weight ratio of the activator to the caprolactam monomer is 0.2-0.3:100.

[0026] In some embodiments of the present invention, the activator is toluene diisocyanate TDI-100, and the weight ratio of the activator to the caprolactam monomer is 0.2:100, 0.25:100 or 0.3:100.

[0027] According to the preparation method of the present invention, in order to make the obtained polyamide-polycarbonate composite material have the advantages of both polyamide and polycarbonate materials and reduce the reaction cost, preferably, the polymerization reaction is divided into two stages: vacuum dehydration and molding. Preferably, the temperature of the vacuum dehydration stage is 120-150°C, the vacuum degree is <-0.1MPa, and the time is 30-60min; preferably, the temperature of the molding stage is 160-200°C, normal pressure, and the time is 30-60min.

[0028] In some embodiments of the present invention, the temperature of the vacuum dehydration stage is 130° C. and the time is 50 min; the temperature of the molding stage is 170° C. and the time is 40 min.

[0029] According to the present invention, the preparation method is specifically:

[0030] Vacuum dehydration:

[0031] (1) melting caprolactam at 120-150° C. to obtain molten caprolactam;

[0032] (2) adding a polycarbonate-solvent solution having a concentration of 0.1-0.4 g / mL to the molten caprolactam, evacuating to a pressure of less than 0.1 MPa, and maintaining the pressure for 30 min to obtain a mixed material I, wherein the solvent is one or more of chloroform, dichloromethane, and tetrahydrofuran;

[0033] (3) adding the catalyst to the mixed material I, and continuing to evacuate the mixture for 20 min until the pressure is less than 0.1 MPa to obtain a mixed material II;

[0034] (4) adding an activator to the mixed material II, stirring and mixing for 30 seconds to obtain a prepolymer;

[0035] (5) polymerizing the prepolymer at 160-200° C. for 30-60 min to obtain the polyamide-polycarbonate composite material.

[0036] In some embodiments of the present invention, in step (1), the melting temperature is 130°C.

[0037] In some embodiments of the present invention, in step (2), the solubility of the polycarbonate-solvent solution is 0.1 g / mL, 0.25 g / mL or 0.4 g / mL.

[0038] In some embodiments of the present invention, in step (2), the solvent is chloroform.

[0039] According to the preparation method of the present invention, in order to promote the dissolution of polycarbonate in chloroform and prevent the volatilization of chloroform, preferably, in step (2), the temperature at which the polycarbonate is dissolved in chloroform is 45-60°C.

[0040] In some embodiments of the present invention, in step (2), the temperature at which the polycarbonate is dissolved in chloroform is 50°C.

[0041] According to the present invention, the preparation method adopts anhydrous and impurity-free environment, under the action of alkaline catalyst, amide monomer is dissociated into amide monomer anion, in addition, amide monomer interacts with activator, obtains monomer containing structure with strong electrophilicity, becomes the center of chain initiation, thereby carries out anionic polymerization, obtains polyamide, and the polyamide prepared by anionic polymerization has higher molecular weight than conventional polyamide prepared by polycondensation, therefore has better physical properties. In the anionic polymerization, the polycarbonate prepared by the added ester exchange method and the generated polyamide undergo ester exchange side reaction, generate polyamide-polycarbonate block copolymer, improve the compatibility between polycarbonate and polyamide, thereby improve the impact strength of block polymer, in addition, the improvement of compatibility between polycarbonate and polyamide, makes the gap in block copolymer material smaller, thereby reduces saturated water absorption. As can be seen from Table 1 in the specific embodiment, under the same preparation process conditions, compared with Comparative Example 1 without adding polycarbonate, the polycarbonate prepared by ester exchange method is added in the preparation process of Example 1 of the present invention, which is conducive to improving impact strength and reducing saturated water absorption.

[0042] The second aspect of the present invention provides a polyamide / polycarbonate composite material prepared according to the preparation method.

[0043] According to the present invention, the IZOD notched impact strength of the polyamide-polycarbonate composite material is 6.7-7.7 kJ / m 2 The saturated water absorption is 3.5-4.6%, and the viscosity-average molecular weight is 78600-83100 g / mol.

[0044] In some embodiments of the present invention, the IZOD notched impact strength of the prepared polyamide / polycarbonate composite material is 7.5 kJ / m 2 、6.7kJ / m 2 , 7.7kJ / m 2 , 7.3kJ / m 2 or 6.9 kJ / m 2 .

[0045] In some embodiments of the present invention, the saturated water absorption rate of the prepared polyamide / polycarbonate composite material is 3.9%, 4.6%, 3.5% or 3.8% respectively.

[0046] In some embodiments of the present invention, the viscosity average molecular weight of the prepared polyamide / polycarbonate composite material is 83100 g / mol, 81900 g / mol, 79500 g / mol, 82700 g / mol or 78600 g / mol, respectively.

[0047] In the present invention, the weight ratio of polyamide, polycarbonate and polyamide-polycarbonate block copolymer in the polyamide / polycarbonate composite material is 89-96.8: 1.8-6.5; 1.4-4.5.

[0048] A third aspect of the present invention provides a component, wherein the component is formed by forming the polyamide / polycarbonate composite material.

[0049] Preferably, the component is selected from one or more of a gear, a propeller, a sealing ring, and an impeller.

[0050] According to the present invention, the component is prepared by the following method: pouring the prepolymer obtained in step (4) of the preparation method provided in the second aspect of the present invention into a mold preheated at a temperature of 160-200°C, and placing the mold in a constant temperature oven at 160-200°C for 30-60 minutes, taking it out, and obtaining the component.

[0051] The following examples are used to illustrate the technical solutions of the present invention, wherein the raw materials and reagents used are commercially available, and the room temperature refers to 15-35°C.

[0052] Transesterified bisphenol A polycarbonate, melt flow rate is 10g / 10min, model is PC02-10.

[0053] Caprolactam, purity 99.9%, purchased from Sinopec.

[0054] Sodium hydroxide, industrial grade, was purchased from Junzheng Energy Chemical Group Co., Ltd.

[0055] Toluene diisocyanate, model TDI-100, was purchased from Nanxing Chemical Co., Ltd.

[0056] The viscosity average molecular weight of the polyamide-polycarbonate composite material was measured by an Ubbelohde viscometer using formic acid as a solvent.

[0057] The IZOD notched impact strength of polyamide-polycarbonate composites was measured according to standard ISO180.

[0058] The saturated water absorption of the polyamide-polycarbonate composite material is measured according to standard GB / T 1034-2008.

[0059] The composition of polyamide-polycarbonate composites was determined by step-by-step dissolution of the composites combined with infrared testing.

[0060] Example 1

[0061] (1) dissolving 5 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0062] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0063] (3) adding 0.15 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0064] (4) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0065] (5) The prepolymer was polymerized at 170° C. for 40 min to obtain a polyamide-polycarbonate composite material I.

[0066] At room temperature, 10 g of the polyamide-polycarbonate composite material I was dissolved and filtered step by step with formic acid and chloroform, respectively, to obtain solution L1, solution L2 and insoluble part S2 in turn, and the solution L1 and solution L2 were heated, volatilized and dried to obtain substances m1 and m2, respectively, and the insoluble part S2 was dried to obtain substance m3; infrared tests were performed on substances m1, m2 and m3, and the test results were as follows: Figure 1-3 As shown, from Figure 1 It can be seen that at 1638cm -1 and 1542cm -1 The characteristic peak of amide appeared at 3300 cm -1 The characteristic peak of amine group appeared at 3070cm -1 、2938cm -1 and 2867cm -1 The characteristic peak of methylene appeared at , indicating that substance m1 is polyamide; Figure 2 It can be seen that at 3015cm -1 and 830cm -1 The characteristic peak of CH appeared at 1774 cm -1 The C=O characteristic peak appeared at 1600 cm -1 The characteristic peak of phenylene appeared at , indicating that substance m2 is polycarbonate; Figure 3 It can be seen that at 1636cm -1 and 1540cm -1 The characteristic peak of amide appeared at 3298 cm -1 The characteristic peak of amine group appeared at 3015cm -1 and 827cm -1 The characteristic peak of CH appeared at 1771cm -1The C=O characteristic peak appeared at , indicating that substance m3 is a polyamide-polycarbonate copolymer. m1, m2 and m3 were weighed respectively, and the weight ratio of polyamide, polycarbonate and polyamide-polycarbonate block copolymer in the polyamide-polycarbonate composite material I was calculated to be 93:4.5:2.5.

[0067] The polyamide-polycarbonate composite material I was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T1034-2008 test, and the test results are shown in Table 1.

[0068] Example 2

[0069] (1) dissolving 2 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0070] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0071] (3) adding 0.2 g of sodium hydroxide to the mixed material I and evacuating the mixture for 20 min to obtain a mixed material II;

[0072] (4) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0073] (5) The prepolymer is polymerized at 170° C. for 40 min to obtain a polyamide-polycarbonate composite material II.

[0074] The components of the polyamide-polycarbonate composite material II were tested in the same manner as in Example 1, and the weight ratio of polyamide, polycarbonate, and polyamide-polycarbonate block copolymer in the polyamide-polycarbonate composite material II was found to be 96.8:1.8:1.4.

[0075] The polyamide-polycarbonate composite material II was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T 1034-2008 test, and the test results are shown in Table 1.

[0076] Example 3

[0077] (1) dissolving 8 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0078] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0079] (3) adding 0.25 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0080] (4) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0081] (5) The prepolymer is polymerized at 170° C. for 40 min to obtain a polyamide-polycarbonate composite material III.

[0082] The components of the polyamide-polycarbonate composite material III were tested in the same manner as in Example 1, and the weight ratio of the polyamide, polycarbonate, and polyamide-polycarbonate block copolymer in the polyamide-polycarbonate composite material III was found to be 89:6.5:4.5.

[0083] The polyamide-polycarbonate composite material III was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T 1034-2008 test, and the test results are shown in Table 1.

[0084] Example 4

[0085] (1) dissolving 5 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0086] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0087] (3) adding 0.15 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0088] (4) adding 0.3 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0089] (5) The prepolymer is polymerized at 170° C. for 40 min to obtain a polyamide-polycarbonate composite material IV.

[0090] The components of the polyamide-polycarbonate composite material VI were tested in the same manner as in Example 1, and the weight ratio of polyamide, polycarbonate, and polyamide-polycarbonate block copolymer in the polyamide-polycarbonate composite material VI was found to be 93.2:4:2.8.

[0091] The polyamide-polycarbonate composite material IV was tested by Ubbelohde viscometer, standard ISO180 test and GB / T 1034-2008 test, and the test results are shown in Table 1.

[0092] Example 5

[0093] (1) dissolving 5 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0094] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0095] (3) adding 0.25 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0096] (4) adding 0.2 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0097] (5) The prepolymer is polymerized at 170° C. for 40 min to obtain a polyamide-polycarbonate composite material V.

[0098] The components of the polyamide-polycarbonate composite material V were tested in the same manner as in Example 1, and the weight ratio of the polyamide, polycarbonate, and polyamide-polycarbonate block copolymer in the polyamide-polycarbonate composite material V was found to be 93:4.4:2.6.

[0099] The polyamide-polycarbonate composite material V was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T1034-2008 test, and the test results are shown in Table 1.

[0100] Comparative Example 1

[0101] (2) melting 100 g of caprolactam at 130° C., and removing the water in the raw material and the chloroform in the solution by vacuuming for 30 min to obtain a mixed material I;

[0102] (3) adding 0.15 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0103] (4) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0104] (5) The prepolymer was polymerized at 170°C for 40 minutes to obtain material A.

[0105] At room temperature, material A is dissolved with formic acid. The material is completely dissolved. The solution is heated to evaporate and dried to constant weight to obtain substance a. Infrared testing of substance a shows that material A is polyamide.

[0106] Material A was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T1034-2008 test, and the test results are shown in Table 1.

[0107] Comparative Example 2

[0108] (1) dissolving 5 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0109] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0110] (3) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material I and rapidly stirring for 10 seconds to obtain a prepolymer;

[0111] (4) The prepolymer was polymerized at 170° C. for 40 min to obtain material B.

[0112] At room temperature, material B is still liquid, indicating that polymerization will not occur in the absence of a catalyst.

[0113] Comparative Example 3

[0114] (1) dissolving 5 g of transesterified bisphenol A polycarbonate in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0115] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0116] (3) adding 0.15 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0117] (4) The mixed material II was polymerized at 170° C. for 40 min to obtain material C.

[0118] At room temperature, the material C sample was not completely cured, indicating that the polymerization reaction proceeded at a low level in the absence of an active agent.

[0119] Material C was tested by Ubbelohde viscometer, standard ISO180 test and GB / T 1034-2008 test, and the test results are shown in Table 1.

[0120] Comparative Example 4

[0121] (1) Dissolve 5 g of phosgene-processed polycarbonate A1100 in 20 mL of chloroform at 50° C. to obtain a polycarbonate-chloroform solution;

[0122] (2) melting 100 g of caprolactam at 130° C., slowly adding the polycarbonate-chloroform solution, and vacuuming for 30 min to remove the water in the raw material and the chloroform in the solution to obtain a mixed material I;

[0123] (3) adding 0.15 g of sodium hydroxide to the mixed material I, and evacuating the mixture for 20 min to obtain a mixed material II;

[0124] (4) adding 0.25 g of toluene diisocyanate TDI-100 to the mixed material II and rapidly stirring for 10 seconds to obtain a prepolymer;

[0125] (5) The prepolymer was polymerized at 170°C for 40 minutes to obtain material D.

[0126] At room temperature, material D was distributed and dissolved using formic acid and chloroform. No insoluble polymer existed, indicating that material D did not contain polyamide-polycarbonate block copolymer.

[0127] Material D was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T1034-2008 test, and the test results are shown in Table 1.

[0128] Comparative Example 5

[0129] Polyamide 6 (PA6 model 1013NW8) and polycarbonate (PC) were vacuum dried at 90°C for 10 h, 3 kg of PA6 and 150 g of PC were weighed and evenly mixed, and melt-blended using a twin-screw extruder (temperature of 240-250°C, screw speed of 200 r / min, feed rate of 50 kg / h), cooled with water, and granulated to obtain material E.

[0130] At room temperature, material E was dissolved step by step with formic acid and chloroform. No insoluble polymer existed, indicating that material E did not contain polyamide-polycarbonate block copolymer.

[0131] At room temperature, material E was subjected to Ubbelohde viscometer measurement, standard ISO180 test and GB / T1034-2008 test, and the test results are shown in Table 1.

[0132] Table 1

[0133]

[0134] Table 1 (continued)

[0135]

[0136]

[0137] It can be seen from the data in Table 1 that no polycarbonate is added in Comparative Example 1. Compared with Example 1, the impact strength of Material A obtained in Comparative Example 1 is lower and the saturated water absorption rate is higher, indicating that adding a small amount of polycarbonate is beneficial to improving the impact strength and reducing the saturated water absorption rate.

[0138] In Comparative Example 2, no sodium hydroxide was added and the reaction could not proceed.

[0139] In Comparative Example 3, TDI-100 was not added, and the activator was lacking, so the reaction proceeded relatively slowly. At the same time, the molecular weight only reached 11200 g / mol.

[0140] In Comparative Example 4, the polycarbonate prepared by the phosgene method is used instead of the polycarbonate prepared by the ester exchange method in Example 1 to prepare a polyamide-polycarbonate composite material. From the data shown in Table 1, it can be seen that compared with the polyamide material prepared without adding polycarbonate in Comparative Example 1, the saturated water absorption rates of the composite materials in Comparative Example 4 and Example 1 are both reduced, and the impact strength of the composite material in Example 1 is greatly increased, but the impact strength of Comparative Example 4 is not significantly improved. This is because the polycarbonate prepared by the phosgene method used in Comparative Example 4 and the polyamide are not fully ester exchanged, so that the compatibility of the two in the prepared polyamide-polycarbonate composite material is still very poor, and the polycarbonate cannot play a toughening role.

[0141] Comparative Example 5 is to obtain a polyamide-polycarbonate composite material by extrusion processing of polyamide and polycarbonate. From the test data, it can be seen that the impact strength of the material decreases and the saturated water absorption rate also increases. This is because the compatibility of polyamide and polycarbonate cannot be completely improved by extrusion processing. The incompatibility of the two phases leads to a decrease in the impact strength of the material. In addition, the incompatibility causes the voids in the material to become larger, which increases the saturated water absorption rate.

[0142] It can be seen from the above embodiments and comparative examples that the preparation method of the present invention realizes the anionic polymerization synthesis of polyamide in an anhydrous and impurity-free environment under the action of a catalyst and an activator, and the obtained polyamide has a higher molecular weight than the conventional polyamide prepared by polycondensation, thereby having better physical properties; in addition, in the anionic polymerization process, the added polycarbonate prepared by the ester exchange method is more likely to undergo an ester exchange side reaction with the generated polyamide to generate a byproduct polyamide-polycarbonate block copolymer, thereby improving the compatibility between polyamide and polycarbonate, thereby improving the impact strength of the block polymer; and the improvement of the compatibility between polyamide and polycarbonate makes the gap in the block copolymer material smaller, thereby reducing the saturated water absorption rate. The polyamide-polycarbonate composite material of the present invention can be used to make structural parts with relatively complex structures.

[0143] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner, but these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a polyamide-polycarbonate composite material, characterized in that: The method comprises: In the presence of a catalyst, molten caprolactam, polycarbonate and an activator are polymerized to obtain the polyamide-polycarbonate composite material.

2. The method according to claim 1, wherein: The polycarbonate is aromatic polycarbonate; and the melt index of the polycarbonate at 300° C. and a load of 1.2 kg is 5-15 g / 10 min.

3. The method according to claim 1 or 2, wherein: The weight ratio of caprolactam to the polycarbonate is 100:2-8.

4. The method according to any one of claims 1 to 3, wherein: The catalyst is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide, and sodium methoxide; And / or, the weight ratio of the catalyst to caprolactam is 0.15-0.25:

100.

5. The method according to any one of claims 1 to 4, wherein: The activator is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl isocyanate, and hexamethylene diisocyanate; And / or, the weight ratio of the activator to caprolactam is 0.2-0.3:

100.

6. The method according to any one of claims 1 to 5, wherein: The polymerization reaction is divided into two stages: vacuum dehydration and molding; The temperature of the vacuum dehydration is 120-150°C, the pressure is less than 0.1MPa, and the time is 30-60min; the temperature of the molding is 160-200°C, the pressure is normal pressure, and the time is 30-60min.

7. The method according to any one of claims 1 to 6, wherein: The method specifically comprises: (1) melting caprolactam at 120-150° C. to obtain molten caprolactam; (2) adding a polycarbonate-solvent solution having a concentration of 0.1-0.4 g / mL to the molten caprolactam, evacuating to a pressure of less than 0.1 MPa, and maintaining the pressure for 30 min to obtain a mixed material I, wherein the solvent is one or more of chloroform, dichloromethane, and tetrahydrofuran; (3) adding the catalyst to the mixed material I, and continuing to evacuate the mixture for 20 min until the pressure is less than 0.1 MPa to obtain a mixed material II; (4) adding an activator to the mixed material II, stirring and mixing for 30 seconds to obtain a prepolymer; (5) polymerizing the prepolymer at 160-200° C. for 30-60 min to obtain the polyamide-polycarbonate composite material.

8. A polyamide-polycarbonate composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The polyamide-polycarbonate composite material according to claim 8, wherein: The IZOD notched impact strength of the polyamide-polycarbonate composite material is 6.7-7.7 kJ / m 2 The saturated water absorption is 3.5-4.6%, and the viscosity-average molecular weight is 78600-83100 g / mol.

10. A component, characterized in that: The component is formed by molding the polyamide-polycarbonate composite material described in claim 8; preferably, the component is selected from one or more of a gear, a propeller, a sealing ring, and an impeller.